1996
DOI: 10.1128/mcb.16.9.4773
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Molecular Chaperone Ydj1 in the Ubiquitin-Dependent Degradation of Short-Lived and Abnormal Proteins in Saccharomyces cerevisiae

Abstract: In Escherichia coli and mitochondria, the molecular chaperone DnaJ is required not only for protein folding but also for selective degradation of certain abnormal polypeptides. Here we demonstrate that in the yeast cytosol, the homologous chaperone Ydj1 is also required for ubiquitin-dependent degradation of certain abnormal proteins. The temperature-sensitive ydj1-151 mutant showed a large defect in the overall breakdown of short-lived cell proteins and abnormal polypeptides containing amino acid analogs, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
124
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 43 publications
3
124
2
1
Order By: Relevance
“…A Saccharomyces cerevisiae cell that harbors a temperature-sensitive mutant of Ydj1 demonstrated a large defect in the overall breakdown of short-lived and abnormal proteins that is mediated by the ubiquitin system. Degradation of long-lived proteins that is mediated by the vacuole and proceeds in a ubiquitin-independent manner was unaffected (25). Interestingly, the effect was specific.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…A Saccharomyces cerevisiae cell that harbors a temperature-sensitive mutant of Ydj1 demonstrated a large defect in the overall breakdown of short-lived and abnormal proteins that is mediated by the ubiquitin system. Degradation of long-lived proteins that is mediated by the vacuole and proceeds in a ubiquitin-independent manner was unaffected (25). Interestingly, the effect was specific.…”
mentioning
confidence: 77%
“…Concomitantly, the ubiquitination of the Ydj1-dependent substrates was significantly reduced. Researchers also found that the chaperone generates a complex with its target substrate, but due to the limitations of the in vivo studies, they could not demonstrate that the complex serves as an essential intermediate in the proteolytic process (25). Degradation of the yeast cyclin Cln3 is also stimulated by Ydj1.…”
mentioning
confidence: 99%
“…Mechanisms of the chaperone effects on prions are not yet completely understood. As some of the chaperones of Hsp70 and Hsp40 families were implicated in targeting misfolded proteins for Ubdependent degradation (30,31), it is possible that some of the effects of chaperones on prions could be mediated by UPS.…”
mentioning
confidence: 99%
“…11 Lysosomes, on the other hand, are membrane bound organellelike structures containing multiple proteases that degrade protein aggregates and membrane proteins. 3,12 Proteins to-be-degraded are transported to the lysosome through e.g., the ATGs/ signaling/regulating systems 13,14 and the following proteolyses are catalyzed by endoproteinases 15,16 that are matured and activated within the lysosome. The resultant peptides continue to break down into amino acids by the lysosomal aminopeptidases and carboxypeptidases, 16,17 and the products (e.g., amino acids and others such as sugars, cholesterols) are then transported back out into the cytosol by the solute transporters in the Requests for materials should be addressed to Yufeng Shen (E-mail: yufeng.shen@pnl.gov) or Richard D. Smith (E-mail: dick.smith@pnl.gov).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Protein degradation has been primarily studied using the methods based on radioactivity, 3 which have proven to be informative on an overall level, but provided little information regarding the degradation steps occurring to individual proteins. Such information currently has been gained by performing in vitro experiments 6,7,[13][14][15][16][17] with individual model proteins/ peptides and proteases, but evidences provided from these in vitro experiments do not represent the true in vivo scenarios due to the inability of a few single proteins to truly mimic the regulatory processes and complexity of degradation occurring to multiple proteins at the same time within a cell.…”
mentioning
confidence: 99%